Fast A‐type currents shape a rapidly adapting form of delayed short latency firing of excitatory superficial dorsal horn neurons that express the neuropeptide Y Y1 receptor. (18th April 2021) - Sinha, Ghanshyam P.; Prasoon, Pranav; Smith, Bret N.; Taylor, Bradley K.
Abstract : Key points: Neuropeptide Y Y1 receptor‐expressing neurons in the dorsal horn of the spinal cord contribute to chronic pain. For the first time, we characterized the firing patterns of Y1‐expressing neurons in Y1eGFP reporter mice. Under hyperpolarized conditions, most Y1eGFP neurons exhibited fast A‐type potassium currents and delayed, short‐latency firing (DSLF). Y1eGFP DSLF neurons were almost always rapidly adapting and often exhibited rebound spiking, characteristics of spinal pain neurons under the control of T‐type calcium channels. These results will inspire future studies to determine whether tissue or nerve injury downregulates the channels that underlie A‐currents, thus unmasking membrane hyperexcitability in Y1‐expressing dorsal horn neurons, leading to persistent pain. Abstract: Neuroanatomical and behavioural evidence indicates that neuropeptide Y Y1 receptor‐expressing interneurons (Y1‐INs) in the superficial dorsal horn (SDH) are predominantly excitatory and contribute to chronic pain. Using an adult ex vivo spinal cord slice preparation from Y1eGFP reporter mice, we characterized firing patterns in response to steady state depolarizing current injection of GFP‐positive cells in lamina II, the great majority of which expressed Y1 mRNA (88%). Randomly sampled (RS) and Y1eGFP neurons exhibited five firing patterns: tonic, initial burst, phasic, delayed short‐latency <180 ms (DSLF) and delayed long‐latency >180 ms (DLLF). When studied at resting membrane potential, most RS neurons exhibited delayed firing, while most Y1eGFP neurons exhibited phasic firing. A preconditioning membrane hyperpolarization produced only subtle changes in the firing patterns of RS neurons, but dramatically shifted Y1eGFP neurons to DSLF (46%) and DLLF (24%). In contrast to RS DSLF neurons, which rarely exhibited spike frequency adaptation, Y1eGFP DSLF neurons were almost always rapidly adapting, a characteristic of nociceptive‐responsive SDH neurons. Rebound spiking was more prevalent in Y1eGFP neurons (6% RS vs . 32% Y1eGFP), indicating enrichment of T‐type calcium currents. Y1eGFP DSLF neurons exhibited fast A‐type potassium currents that are known to delay or limit action potential firing and exhibited smaller current density as compared to RS DSLF neurons. Our results will inspire future studies to determine whether tissue or nerve injury downregulates channels that contribute to A‐currents, thus potentially unmasking T‐type calcium channel activity and membrane hyperexcitability in Y1‐INs, leading to persistent pain. Key points: Neuropeptide Y Y1 receptor‐expressing neurons in the dorsal horn of the spinal cord contribute to chronic pain. For the first time, we characterized the firing patterns of Y1‐expressing neurons in Y1eGFP reporter mice. Under hyperpolarized conditions, most Y1eGFP neurons exhibited fast A‐type potassium currents and delayed, short‐latency firing (DSLF). Y1eGFP DSLF neurons were almost always rapidly adapting and often exhibited rebound spiking, characteristics of spinal pain neurons under the control of T‐type calcium channels. These results will inspire future studies to determine whether tissue or nerve injury downregulates the channels that underlie A‐currents, thus unmasking membrane hyperexcitability in Y1‐expressing dorsal horn neurons, leading to persistent pain.